NEGARA ISLAM - Ihsan Satrya Azhar (Hijri, 2017)
This article is about the Islamic state. The need of some Islamists to set up the islamic state has been rising since political revolution in Iran. The big question in this issue is that does Islam has a concept of Islamic state and does it order his embracers to set the islamic state? There were three major opinions in this issue, first, who rejected the idea of Islamic state at all, some of them are Ali Abdul Raziq and Ali Ashgar Engineer; second, who accepted the idea of Islamic state, like Abul A’la Al-Ma’ududi and; third, who said that Islam didn’t order specifically but the condition made it as a compulsory things, they are Hasan Al-Banna, Sayyid Qutb and Abdul Qodir Audah.